2018 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--29992
|View full text |Cite
|
Sign up to set email alerts
|

Board 25: Work in Progress: Mandatory Attendance in Office Hours to Improve Students’ Learning Experience

Abstract: is a Ph.D. student in Biomedical Engineering at The University of Akron. He has also served as a research assistant in Cleveland Clinic Akron General since 2016, where he conducts research on biomechanics of human knee joint and patellar instability. In 2016, he received a doctoral teaching fellowship from the College of Engineering at The University of Akron. Through this teaching program, he has served as an instructor for several undergraduate-level courses, and he has conducted educational research on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…A study by Guerrero and Rod found that for each office hour attended students saw a 0.77% increase in their grade even correcting for overall GPA, gender, race, and family income [3]. A study by Rezvanifar and Amini found that students who were required to attend office hours after failing a first exam improved their grades on future exams, which was not true for students who were not required to attend office hours [4]. Despite evidence of office hour utilization improving student performance, office hours are generally under-utilized.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Guerrero and Rod found that for each office hour attended students saw a 0.77% increase in their grade even correcting for overall GPA, gender, race, and family income [3]. A study by Rezvanifar and Amini found that students who were required to attend office hours after failing a first exam improved their grades on future exams, which was not true for students who were not required to attend office hours [4]. Despite evidence of office hour utilization improving student performance, office hours are generally under-utilized.…”
Section: Introductionmentioning
confidence: 99%